The link between strength of lattice preferred orientation, second phase content and grain boundary migration: A case study from the Alpine Fault zone, New Zealand. (December 2015) - Little, Timothy A.; Prior, David J.; Toy, Virginia G.; Lindroos, Zoe Reid
Abstract: We analyse the microstructure and quartz LPOs of 36 layers of varying composition from a several-meter thick sequence of amphibolite-facies metacherts and related mica-garnet-plagioclase-quartz bearing schists from the central Southern Alps in the mylonite zone related to the Alpine Fault. Quartz contents vary from ∼10 to 100% and all of the LPO fabric skeletons are similar, featuring an asymmetric single girdle of [c]-axes inclined ∼30° away from the ZY plane. LPO strength is typically low at quartz contents <70% (M Index of ∼0.05) whereas it may be very high for nearly pure quartz rocks (M Index of up to 4.0). We attribute this change to a sparseness of interphase boundaries in the more quartzose rocks, a reduction in grain-boundary pinning, and a corresponding efficiency of grain boundary migration during dynamic recrystallization. The transition corresponds to a Zener parameter of approximately 700. In layers poor in quartz and rich in mica, the quartz grain size was kept small, and phase-boundary density, high. This may have promoted grain-size sensitive creep and dislocation glide in mica. Dislocation creep in the interspersed quartz grains was correspondingly reduced, and weaker quartz LPOs were produced. In highly quartzose layers, quartz grain boundaries experienced little drag or pinning from impurity phases and were able to migrate quickly into higher strain-energy grains. Preferential consumption of poorly oriented grains strengthened quartz LPOs, geometrically softened the dislocation creep process in these quartzose layers, and contributed to grain coarsening. The lack of evidence for instabilities in the thinly layered (<1 mm, quartz-rich vs. mica-rich) mylonite implies that a combination of deformation mechanisms, grain-size sensitive flow and dislocation creep, in the layers were able to accommodate a nearly homogeneous deformation between the different composition layers. Highlights: LPO strength and grain size increase with quartz content, most rapidly above ∼70%. Where interphase boundaries are few, GBM strengthens quartz LPOs and weakens the rock. Where interphase boundaries are many, pinning occurs, quartz LPOs are weak, and GSS creep dominates. GBM may lead to dynamic growth of large, well-oriented quartz grains.